2021
DOI: 10.1002/fsn3.2531
|View full text |Cite
|
Sign up to set email alerts
|

The sensory and flavor characteristics of Shaoxing Huangjiu (Chinese rice wine) were significantly influenced by micro‐oxygen and electric field

Abstract: Chinese rice wine (Huangjiu), a traditional Chinese alcohol beverage, is popular among Chinese customers. Huangjiu, as a traditional alcoholic beverage with high nutritional value and unique flavor, has a history of several centuries in East Asia (Shen et al., 2012). Huangjiu is made from wheat and other grains as raw materials, using Wheat Qu, rice Qu, or alcoholic medicine as saccharifying agent, and after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The sensory characteristics of BH were examined by a sensory evaluation panel consisting of 11 (6 men and 5 women) winetasters according to the Chinese standard (GB/T 13662-2018) and (Shen et al, 2021). The four aspects evaluated were appearance (0-10 score), aroma (0-30 score), taste (0-40 score), and typicalness (0-20 score; Table 1).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The sensory characteristics of BH were examined by a sensory evaluation panel consisting of 11 (6 men and 5 women) winetasters according to the Chinese standard (GB/T 13662-2018) and (Shen et al, 2021). The four aspects evaluated were appearance (0-10 score), aroma (0-30 score), taste (0-40 score), and typicalness (0-20 score; Table 1).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The X variable is relative abundance of bacterial community. The Y variable is the average concentration of flavor substances (Shen, Zhu, et al., 2021; Shen, Wu, et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Huangjiu is a complex mixture composed of hundreds of flavor compounds. The aroma of Huangjiu is one of the decisive factors affecting consumers’ sensory quality and purchase (Shen, Zhu, et al., 2021; Shen, Wu, et al., 2021; Welke et al., 2014). The aroma components of Huangjiu wine mainly come from raw materials, substances decomposed by various enzymes, and microbial metabolites in the brewing process (Chen & Xu, 2013; Shen, Li, et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon revealed that the application of external PEF affected the molecular structure and chemical reactions among the substances in wine ( 81 ). Similarly, the fatty acids such as isovaleric acid, hexanoic acid, and octanoic acid in Chinese rice wine treated with PEF (2 kV/cm, 0.5 Hz, 36 pulses) could reach the level of natural aging for 3 years ( 82 ).…”
Section: Applicability Of Pulsed Electric Fieldmentioning
confidence: 99%